Activity report of the 53rd Japanese Antarctic Research Expedition (JARE-53) wintering party in 2012-2013 - Kenji Ishizawa (National Institute of Polar Research, 2015)
The JARE-53 wintering party conducted the second year of the research and logistical program of the six-year plan of Japanese Antarctic Program Phase VIII following the handover from the JARE-52 wintering party on 12 February 2012. Because the icebreaker Shirase could not anchor at Syowa Station due to thick sea ice and snow, some of the fuel and supplies were left on the ship. However, the wintering activities were not affected by any major adverse events. JARE-53 conducted comprehensive observations of the Antarctic atmosphere as one of the prioritized observation projects named "Earth's Environmental Change Revealed by Observing the Antarctic Middle and Upper Atmosphere". Logistics facilities at the station experienced no major problems and the electricity generators performed reliably. There was no serious blizzard-related damage and no physical injuries to personnel during the wintering period. Four members undertook a round-trip traverse to Dome Fuji Station led by the JARE-54 summer party, carrying out astronomical observations and other tasks. Sea-ice thickness and snow depth were measured near the intended routes of the icebreaker Shirase; however, the vessel was again unable to anchor at the Station. JARE-53 handed over the operation of the station to JARE-54 on 1 February 2013.